Resident Wild Birds: A Potential Source for Fluoroquinolone-resistant E. coli (Journal of Science and Technology Research, 2024)
Antibiotic resistance, commonly known as antimicrobial resistance, is a major global health concern. In Bangladesh, resident wild birds such as the house crow, common myna, and house sparrow can be found near human settlements all year. As a result, these birds could carry fluoroquinolone-resistant Escherichia coli. We collected 134 freshly dropped fecal samples for this study. E. coli was confirmed using morphological characteristics from culture plates as well as PCR. The Antibiogram of the target isolates was determined by a disk diffusion method and the presence of any resistant genes in the isolates was determined by PCR. About 83% of the common wild birds were found positive for E. coli in their fecal samples. In the antibiogram study about 16 to 40% of isolates were found resistant to different fluoroquinolones. Forty-five percent of isolates were found to carry the fluoroquinolone-resistant gene qnrA, whereas the qnrS gene was absent in all the isolates. All of the isolates examined were found to be resistant to ampicillin and ceftazidime. There are no published data on fluoroquinolone-resistant E. coli isolated from common resident wild birds in Bangladesh. Our data imply that house crow, common myna, and house sparrow could be a possible source for the spread of fluoroquinolone-resistant E. coli in the environment. J. of Sci. and Tech. Res. 6(1): 83-88, 2024